2007
DOI: 10.1085/jgp.200609672
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-Function Mutations in the MEC-4 DEG/ENaC Sensory Mechanotransduction Channel Alter Gating and Drug Blockade

Abstract: MEC-4 and MEC-10 are the pore-forming subunits of the sensory mechanotransduction complex that mediates touch sensation in Caenorhabditis elegans (O'Hagan, R., M. Chalfie, and M.B. Goodman. 2005. Nat. Neurosci. 8:43–50). They are members of a large family of ion channel proteins, collectively termed DEG/ENaCs, which are expressed in epithelial cells and neurons. In Xenopus oocytes, MEC-4 can assemble into homomeric channels and coassemble with MEC-10 into heteromeric channels (Goodman, M.B., G.G. Ernstrom, D.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
53
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 36 publications
13
53
0
Order By: Relevance
“…Consistent with the previously reported current-suppressing effect of MEC-10( þ ) on MEC-4(d) currents, 11,13,20 we find that the coexpression of MEC-4(A149V) with MEC-10( þ ) is associated with currents that are smaller relative to MEC-4(A149V) alone. If the native MEC-4(A149V) þ MEC-10( þ ) channel has altered electrophysiological properties in vivo, changes are not substantial enough to disrupt the function in touch sensation, as the mec-4(bz301) mutant is touch sensitive and mec-4 function is required for this behavior (Figure 4b).…”
Section: Mec-4(a149v) Increases Nasupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the previously reported current-suppressing effect of MEC-10( þ ) on MEC-4(d) currents, 11,13,20 we find that the coexpression of MEC-4(A149V) with MEC-10( þ ) is associated with currents that are smaller relative to MEC-4(A149V) alone. If the native MEC-4(A149V) þ MEC-10( þ ) channel has altered electrophysiological properties in vivo, changes are not substantial enough to disrupt the function in touch sensation, as the mec-4(bz301) mutant is touch sensitive and mec-4 function is required for this behavior (Figure 4b).…”
Section: Mec-4(a149v) Increases Nasupporting
confidence: 92%
“…has been electrophysiologically characterized in Xenopus oocytes 10,11,13,20 (see also Figure 5a). In brief, this work showed that (1) channels including the MEC-4(d) subunit conduct markedly elevated Na þ and Ca 2 þ currents relative to MEC-4( þ ) channels (note that MEC-4( þ ) conducts only barely detectable currents); (2) MEC-10( þ ) and MEC-10(d) do not conduct current as homomeric channels; (3) MEC-10 is not essential for MEC-4(d) channel conductance and dampens MEC channel currents when present; and (4) stomatin MEC-2 and paraoxonaserelated MEC-6 subunits increase current.…”
Section: Mec-4(a149v) Increases Namentioning
confidence: 99%
“…MEC-4 can form either a homomeric channel by itself or heterotrimeric channels with MEC-10, comprising two MEC-4 subunits and a MEC-10 subunit (7). Together, they form a channel that is permeable to Na ϩ and Ca 2ϩ (8,9) and sensitive to amiloride and specific amiloride derivatives (10).…”
mentioning
confidence: 99%
“…Second, MEC-2 and MEC-6 increased the activity of MEC-4(d) channels 5 d after injection of their cRNAs into Xenopus oocytes without apparently changing the amount of surface-localized MEC-4(d) protein (8)(9)(10)(11). [The dominant mec-4(d) mutation, which results in an A713T substitution, produces a hyperactive channel that is constitutively active (9,12,13) and leads to TRN degeneration.] Third, MEC-2 and MEC-6 coimmunoprecipitated with MEC-4(d), MEC-10, and each other in heterologous cells (8)(9)(10).…”
mentioning
confidence: 99%